2018
DOI: 10.1021/acs.jpcb.7b10254
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Critical Role Played by Ado762′OH in the Post-Transfer Editing by Archaeal Threonyl-tRNA Synthetase

Abstract: Archaeal threonyl-tRNA synthetase (ThrRS) possesses an editing active site wherein tRNA that has been misaminoacylated with serine (i.e., Ser-tRNA) is hydrolytically cleaved to serine and tRNA. It has been suggested that the free ribose sugar hydroxyl of Ado76 of the tRNA (2'OH) is the mechanistic base, promoting hydrolysis by orienting a nucleophilic water near the scissile Ser-tRNA ester bond. We have performed a computational study, involving molecular dynamics (MD) and hybrid ONIOM quantum mechanics/molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…We further suggested that the ribozymal mechanism that we discovered is common in the editing reaction of various aaRS systems beyond the classes ( Table 1) [63]. In fact, Thermus thermophilus IleRS (class Ia) [77], Pyrococcus abyssi ThrRS (class IIa) [72,74,75,78], and Enterococcus faecalis ProRS (class IIa) [71] showed the similar binding mode of the nucleophilic water in the catalytic site. Furthermore, Kumar et al also suggested that the editing reaction of the complex of prolyl-tRNA synthetase (ProRS) and alanyl-tRNA Pro exhibited a similar mechanism, in which the 2 0 -OH group of A76 of tRNA Pro was involved in the substrate binding and the activation of the nucleophilic water [71].…”
Section: Ab Initio Qm/mm MD Simulation Of Editing Reactionmentioning
confidence: 67%
“…We further suggested that the ribozymal mechanism that we discovered is common in the editing reaction of various aaRS systems beyond the classes ( Table 1) [63]. In fact, Thermus thermophilus IleRS (class Ia) [77], Pyrococcus abyssi ThrRS (class IIa) [72,74,75,78], and Enterococcus faecalis ProRS (class IIa) [71] showed the similar binding mode of the nucleophilic water in the catalytic site. Furthermore, Kumar et al also suggested that the editing reaction of the complex of prolyl-tRNA synthetase (ProRS) and alanyl-tRNA Pro exhibited a similar mechanism, in which the 2 0 -OH group of A76 of tRNA Pro was involved in the substrate binding and the activation of the nucleophilic water [71].…”
Section: Ab Initio Qm/mm MD Simulation Of Editing Reactionmentioning
confidence: 67%
“…2,17,18 Indeed, water-assisted mechanism is well-known approach in facilitating the reaction in other fundamental enzymes. 19,20 Cytochrome c peroxidase (Ccp1) served for decades as a benchmark biochemical model for understanding the chemical and structural properties of other peroxidases. 6 Its principal function is to eliminate the toxic H 2 O 2 from the cell with the assistance of its redox partner cytochrome c (Cc).…”
Section: Introductionmentioning
confidence: 99%
“…2,17,18 Indeed, water-assisted mechanism is well-known approach in facilitating the reaction in other fundamental enzymes. 19,20…”
Section: Introductionmentioning
confidence: 99%